On the importance of modeling gold nanoparticles distribution in dose-enhanced radiotherapy - Rasouli FS (Dove Medical Press, 2019)
Fatemeh S Rasouli,1 S Farhad Masoudi,1 Somayeh Asadi21Department of Physics, K.N. Toosi University of Technology, Tehran, Iran; 2Department of Mechanical Engineering, Politecnico Di Milano, Milan, ItalyPurpose: To investigate the effect of precise modeling for Monte Carlo simulations of gold nanoparticles (GNPs) dose-enhanced radiotherapy, two models characterized by their distribution of GNPs in a simulated macroscopic cubic tumor were introduced. The motivation was the widely documented tendency of GNPs to localize around the cell nucleus.Methods: The introduced models composed of 2.7×107 ellipsoid cells, each of them containing a centrally located nucleus as the target for dose evaluation. In the first model, the spheres of GNP are homogeneously distributed in the whole tumor volume, and in the latter, GNPs are localized in the cytoplasms surrounded the nuclei.Results: The results achieved through applying Monte Carlo radiation transports using the Mont Carlo N-Particle eXtended code (MCNPX) show an underestimation of nuclear dose enhancement caused by homogeneous model compared with that of heterogeneous distribution. By investigating various quantities, it was found that subcellular location of GNPs strongly governs the sensitivity of dose enhancement to the number and concentration of GNPs targeted in the tumor. Other obvious differences are revealed by studying the dose enhancement curves in depth of the tumor. While the heterogeneous model predicts an approximately constant dose enhancement in depth for primary photon energies of 50 keV and more, the homogeneous model estimates an energy-dependent increase of about 11 to 30%.Conclusion: It can be concluded that defining a model in accordance with the experimental observations can effectively account for accurate prediction of macroscopic dose enhancement in the target of interest.Keywords: gold nanoparticles, dose-enhanced radiotherapy, cell model, tumor, Monte Carlo simulation